Analisis Kebijakan Penataan Ruang Kota Jayapura Terhadap Luasan Hutan Kota di Distrik Abepura - Sonny Iyai; Sudiro Sudiro; Tommi Tommi (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
Jayapura City There is Abepura District which has supporting economic infrastructure so that economic growth in Abepura District is very rapid. The existing city forests in several locations in Abepura District need to be improved or expanded to improve their function. This study aims to see the spatial planning policy in Jayapura City related to the area of ​​the Abepura District city forest, analyze the implications of the Jayapura City spatial planning policy on the area of ​​the Abepura District City Forest, and Analyze the Suitability of Abepura District City Forest Land. This research method uses qualitative descriptive analysis and Spatial Analysis to obtain a picture of the area of ​​the Abepura District City Forest as well as a picture of land conversion and the suitability of the Abepura District City Forest land. The results of this study are that the area of ​​​​Approximately 997 hectares of City Forest is in Abepura District According to the 2014 Jayapura City Spatial Policy Data, the City Forest Development policy has only been carried out once in Organda over the past few years, while policies that reduce the area of ​​​​City Forest Many are carried out in housing, building and road development activities, this is because on average the development already has a land permit and a building permit. This study provides an overview that the problem of the reduced area of ​​the Abepura District City Forest occurs because the Jayapura City Government is not firm enough in implementing the Jayapura City Spatial Planning Policy in development so that it is in accordance with the Area Designation.